2015
DOI: 10.11622/smedj.2015185
|View full text |Cite
|
Sign up to set email alerts
|

The clinical presentation and diagnosis of ketamine-associated urinary tract dysfunction in Singapore

Abstract: Ketamine is a short-acting anaesthetic agent that has gained popularity as a 'club drug' due to its hallucinogenic effects. Substance abuse should be considered in young adult patients who present with severe debilitating symptoms such as lower urinary tract symptoms, even though the use of controlled substances is rare in Singapore. Although the natural history of disease varies from person to person, a relationship between symptom severity and frequency/dosage of abuse has been established. It is important t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 9 publications
(19 reference statements)
1
19
0
1
Order By: Relevance
“…A previous study suggested that patients with interstitial cystitis/bladder pain syndrome (IC/BPS) and KU have similar clinical presentations and histological findings, such as mucosal inflammation with urothelial denudation . We further found that the inflammation in bladders with KU also involves the muscle and subserosal layers of the bladder.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…A previous study suggested that patients with interstitial cystitis/bladder pain syndrome (IC/BPS) and KU have similar clinical presentations and histological findings, such as mucosal inflammation with urothelial denudation . We further found that the inflammation in bladders with KU also involves the muscle and subserosal layers of the bladder.…”
Section: Discussionsupporting
confidence: 58%
“…A previous study suggested that patients with interstitial cystitis/bladder pain syndrome (IC/BPS) and KU have similar clinical presentations and histological findings, such as mucosal inflammation with urothelial denudation. 16 We further found that the inflammation in bladders with KU also involves the muscle and subserosal layers of the bladder. The histopathological changes in bladders with KU are more similar to eosinophilic cystitis (EC), which is characterized by bladder wall thickening, an eosinophilic predominant pancystitis, and may involve ureter change.…”
Section: Discussionmentioning
confidence: 59%
“…Urine culture is usually negative. Sterile pyuria, red blood cells and proteinuria can be present at urinalysis 68 . Urine cytology is negative 3,4,60 .…”
Section: Evidencementioning
confidence: 99%
“…Unlike first-time users of ketamine, patients with a history of chronic ketamine use commonly reported abdominal pain and urinary tract symptoms (Skeldon and Goldenberg, 2014). A number of cases reports suggest that ketamine abuse can cause suprapubic pain, dysurria and hematuria (Mason et al, 2010;Peng et al, 2014;Yek et al, 2015). Radiology results revealed decreased bladder volume, bladder wall thickening, musosal enhancement, dilation of ureter, and perivesical inflammation in ketamine abusers Wu et al, 2012).…”
Section: Psychological and Physiological Effects Of Ketaminementioning
confidence: 99%